Neinvazivni prenatalni testovi za skrining hromozomskih abnormalnosti u in vitro oplodnji starijih trudnica u severozapadnoj Kini: NIPT for chromosomal abnormality in northwest China - Xue, Shuyuan; Wang, Lixia; Yu, Zhen; Zhu, Jingying; Feng, Le; Din, Guifeng; Dai, Penggao (Journal of Medical Biochemistry, 2025)
Background: The study aimed to explore the value of using non-invasive prenatal tests (NIPT) in the second trimester of pregnancy for chromosomal abnormality screening in vitro fertilization in elderly pregnant women and to analyze the reasons for inconsistent screening results in northwest China. Methods: A total of 47,286 pregnant women aged 19-51 who underwent prenatal examinations were collected. NIPT detection found that the positive rate of pregnant women aged >35 with spontaneous pregnancy was 0.78%, and the positive rate of in vitro fertilization pregnancy was 0.82%. Then, the detection accuracy of NIPT for pregnant women aged >35 with in vitro fertilization was further analyzed. Results: NIPT’s sensitivity, specificity, and positive predictive value in detecting common chromosomal aneuploidies (T21, T18, and T13) in pregnant women aged >35 who received in vitro fertilization were 99.72%, 99.78%, and 66.45%, respectively. The mean gestational age, pregnancy number, AFP, and free β-HCG significantly differed between the positive and false positive groups (P < 0.05). Logistic analysis showed that the mean gestational age and AFP were independent risk factors for the failure of NIPT diagnosis (P < 0.05). Conclusions: NIPT has a particular detection performance for common chromosomal aneuploidies in vitro fertilization in pregnant women. However, factors affecting detection accuracies must be considered when using it.